Productive Waqf Management Model to Improve Education System at the Raudhatul Ulum Islamic Boarding School in Lumajang - Khoirus Sholeh (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2023)
This study examines the management of productive waqf to improve the efficiency and effectiveness of the education system at the Raudhatul Ulum Islamic Boarding School in Lumajang. This research approach implemented a qualitative case study design. Data were obtained through in-depth interviews, observations, document analysis, and focus group discussions. This research approach implemented a qualitative case study design. Data were obtained through in-depth interviews, observations, and document analysis. The results indicate that productive waqf plays a significant role in increasing the Islamic boarding school’s financial independence, thereby contributing to a more optimal allocation of resources for operations. The Raudhatul Ulum Islamic Boarding School has implemented a performance-based budgeting system, where every expenditure must be linked to the achievement of predetermined educational targets.